Comparison of visual spatial cognitive abilities and working memory capacity in children with different levels of digital game addiction - Yılmaz, Selin; Bozyiğit, Tuğba (Journal of Dependence, 2023)
Objective: The goal of the research was to scrutinize association between digital game addiction level and visuospatial cognitive skill and working memory performance of children aged 10-14 who played video games. Method: The sample group of the study composed of 98 (36 female and 62 male) children with a mean age of 12.35 (SD=0.75). Data measurement tools were Information Form, Digital Game Addiction Scale for Children, Wechsler Memory Scale-III Letter-Number Sequencing Subtest and Clock Drawing Test. Results: According to the One-Way ANOVA analysis results, while the Clock Drawing Test score increased in the risky group compared to the low-risk group, this test performance was found to be lower in the addicted group compared to the risky group. Similarly, Letter-Number Sequencing Test score increased in the risky group compared to the low-risk group, this test performance was found to be lower in the addicted group compared to the risky group. Conclusion: Playing video games can increase visuospatial skills and working memory performance of children, but as addiction increases, these skills may be impaired. Thus, it is recommended that training programs to children can be created to provide in order to more qualified and limited time use of video games.